2011
DOI: 10.1542/peds.2010-3218
|View full text |Cite
|
Sign up to set email alerts
|

Are Parents of Young Children Practicing Healthy Nutrition and Physical Activity Behaviors?

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Becoming a parent is a common life event in early adulthood, but little is known about the connection between parenthood and weight-related health. Understanding parents' health behaviors is important, because health habits may be perpetuated into adulthood and transmitted to children. WHAT THIS STUDY ADDS:Results of this study shed light on the relationship between parenthood and weight status, dietary intake, and physical activity in both mothers and fathers and indicate that mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 25 publications
4
109
2
1
Order By: Relevance
“…42 Living with the participating child' s father was not associated with maternal activity at any intensity here, although limited heterogeneity in this exposure may in part account for this finding. As mothers tend to be less active than fathers (and men), 10 and consume a less healthy diet than women without children, 11 mothers of young children may be at greater risk of negative health outcomes and remain a target for health promotion interventions in their own right.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…42 Living with the participating child' s father was not associated with maternal activity at any intensity here, although limited heterogeneity in this exposure may in part account for this finding. As mothers tend to be less active than fathers (and men), 10 and consume a less healthy diet than women without children, 11 mothers of young children may be at greater risk of negative health outcomes and remain a target for health promotion interventions in their own right.…”
Section: Discussionmentioning
confidence: 99%
“…Having appraised the evidence of activity in young children, 14,41 and mothers of young children, 10,11,42 a range of other variables were used. Hour, time of the day, and week were obtained from the accelerometer output.…”
Section: Physical Activity Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bassett-Gunter et al (2013) found that both new and established fathers report greater intentions to eat healthily than do men without children. Berge et al (2011) reported that young adult mothers had poorer dietary intakes compared with women without children. The authors concluded that there may be conflicting factors influencing dietary behaviour in mothers: they may want to model good nutrition but at the same time, have less available time to eat healthily (Berge et al 2011).…”
Section: Dietmentioning
confidence: 99%
“…Parenthood is associated with more sedentary lifestyles in both fathers and mothers (4,6), and typically mothers were less active than fathers (4).…”
Section: Introductionmentioning
confidence: 99%